If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -14x = 3x + 8x + -18 Combine like terms: 7x + -14x = -7x -7x = 3x + 8x + -18 Reorder the terms: -7x = -18 + 3x + 8x Combine like terms: 3x + 8x = 11x -7x = -18 + 11x Solving -7x = -18 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. -7x + -11x = -18 + 11x + -11x Combine like terms: -7x + -11x = -18x -18x = -18 + 11x + -11x Combine like terms: 11x + -11x = 0 -18x = -18 + 0 -18x = -18 Divide each side by '-18'. x = 1 Simplifying x = 1
| -29+n=9 | | 8y+15=12y-9 | | 5/2x-11/2=19/2 | | 23=-14+r | | 4x-7+6x-13=180 | | a-28=28 | | 9(d-2)+2= | | 5.5-4.72x-1.3x=30.784 | | 9(2x-8)=0 | | q+12=23 | | 2w+5+2w-10=90 | | 5+q=28 | | x^3-5x^2+4x=20 | | 6y-8=16 | | 1/6(m-1)=2/3(m+2)-1/3m | | 7y-9=180 | | 28=a+27 | | (9x-5)=47 | | -3(m+5)= | | 26-2(x+3)=32 | | z+4=20 | | 3x/4+2=4z-1 | | y=4x^2-9 | | -6(5x-2y+7)= | | 12-3x=27+2x | | 7x^2=26x-15 | | -11x+8=-36 | | 30-5+(-5)= | | 2(x-2)-3(4x-1)=0 | | -(3x-5y+3)= | | 2.00+35*.30=x | | 9y^2-169x^2= |